Spatial Distribution and Source Apportionment of Heavy Metals in Soils of Gebeng Industrial City, Malaysia - Nasly, Mohamed Ali; Hossain, Mohamed Amjed; Islam, Mir Sujaul (Springer-Verlag Berlin Heidelberg, 2015)
Heavy metal concentrations were examined in 30 soil samples from Gebeng industrial city, Malaysia using inductively coupled plasma–mass spectrometry for As, Ba, Cd, Co, Cr, Cu, Ni, Pb and Zn, and direct mercury analyzer (DMA-80) for Hg. Multivariate statistical techniques including hierarchical cluster analysis (CA), principal component analysis (PCA), correlation analysis and analysis of variance were used to identify the spatial distribution and potential sources of heavy metals. The mean concentrations of heavy metals in the soil samples are in decreasing order as follows: Co[Ba[Zn[As[Pb[Cr[Cu[Ni[Hg[Cd. The Gebeng soils are characterized by high mean relative concentration of As, Ba, Cd, Co, Cr, Cu, Hg, Ni, Pb and Zn in the industrial zone (IZ) than the Kampung-Balok residential area (KB) and submerged area (SA), indicating inputs from industrial activities. Geochemical results suggested that Gebeng soils are primarily polluted by As, Co, Hg, Pb, and Cu subsequently derived from anthropogenic sources. PCA and CA in the heavy metals indicate both anthropogenic and natural origin. However, the geoaccumulation index and pollution load index further confirm the high contamination levels of the heavy metals in IZ and low to uncontaminated in KB and SA regions.